INSTAGRAM SOCIAL MEDIA ANALYSIS OF TEENAGER LIFESTYLE AT SMA BINTARA DEPOK - Rina Astriani; Ahyad Ahyad (Asosiasi Dosen Muda Indonesia, 2022)
This study aims to find out how social media Instagram @anyageraldine affects the lifestyle of teenager at SMA Bintara Depok. Researchers use qualitative methods because they want to explore facts, symptoms, and events that influence social media on adolescent behavior in the field as it is in the context of space and time and the natural environment of teenager. The research instrument used was interviews with 5 informants who were taken using Cognitive Social Theory. The results of this study indicate that the informant prefers to follow the fashion style of anyageraldine which is fashionable rather than following her fullgar lifestyle. besides that the informant also wanted to be famous and successful like Anyageraldine. Instagram @anyageraldine not only posts full-length photos and videos, but there are also endorsed photos such as clothes, make-up, sneakers, and others. But the main thing is a positive lifestyle to be liked and followed by teenagers.